Implementation of Financial Management Functions in Schools - Wisnu Yuli Setianingsih; Nofi Wulandari; Nurkolis Nurkolis (Universitas Negeri Malang, 2025)
Abstract: The complexity of financial management in educational institutions requires the implementation of systematic management functions to achieve optimal effectiveness. This study aims to analyze the implementation of the four financial management functions planning, organizing, directing, and controlling in improving the performance of school financial management. The research methodology employs a qualitative approach with a descriptive-analytical literature study design through a systematic review of relevant academic literature. Secondary data analysis is conducted using content analysis with categorization based on the four dimensions of financial management functions. The results indicate a significant transformation from conventional approaches toward integrated, performance-based systems. The implementation of the planning function produces more accurate budget documents through participatory approaches. The organizing function establishes hierarchical structures with clear division of responsibilities, reducing the risk of fund misappropriation. Transformational leadership within the directing function enhances team motivation and stakeholder participation. Information technology–based controlling functions facilitate real-time monitoring and reporting transparency. The conclusion shows that the synergistic integration of the four management functions creates a holistic framework that substantially improves the effectiveness of school financial management. Keywords: Financial management; educational institutions; management functions